2011
DOI: 10.3174/ajnr.a2606
|View full text |Cite
|
Sign up to set email alerts
|

Tectorial Membrane Injury: Frequently Overlooked in Pediatric Traumatic Head Injury

Abstract: SUMMARY:REHs and tectorial membrane injuries are rare complications of pediatric head and neck injuries. We aim to describe the neuroimaging findings in pediatric REHs, to summarize the mechanism of injury, and to correlate the imaging findings with the clinical presentation. We retrospectively evaluated CT and/or MR imaging studies of 10 children with traumatic REH. Most patients were involved in MVAs. The tectorial membrane was injured in 70% of patients, and REHs were medium to large in 80%. None of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Tectorial membrane injury is manifest by discontinuity of the normal T2 hypo-intense signal of the ligament, increase of the T2 signal intensity or if the intact membrane is elevated by a REH. 2 Complete assessment of the CCJ ligaments must include those listed in Fig 1. Review of the literature indicates that this entity is under-diagnosed. Suspicion by the treating clinician and equally by the reporting radiologist is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Tectorial membrane injury is manifest by discontinuity of the normal T2 hypo-intense signal of the ligament, increase of the T2 signal intensity or if the intact membrane is elevated by a REH. 2 Complete assessment of the CCJ ligaments must include those listed in Fig 1. Review of the literature indicates that this entity is under-diagnosed. Suspicion by the treating clinician and equally by the reporting radiologist is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Retroclival hematomas were first described by Orrison et al [2] in 1986 and have been subsequently noted in occasional case reports [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and small series [20][21][22][23]. Most retroclival epidural and subdural hematomas occur in children, and these collections are almost always reported in the context of accidental trauma, particularly motor vehicle accidents [19,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Children with retroclival epidural hematomas occurring in the setting of accidental trauma often present with neurological deficits ranging from lower cranial nerve paresis to tetraplegia and loss of spontaneous respiration [21][22][23]28]. Children with retroclival subdural hematomas arising from accidental injury may present with hemiparesis and respiratory arrest but children can also be asymptomatic [27,30,32].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] However, studies in children, who are much more susceptible to atlanto-occipital injury than adults, 11,12 suggest a more essential role of MR imaging in the correct diagnosis of otherwise occult injuries at the craniocervical junction. 13,14 In 1 study of subjects younger than 18 years of age, Junewick et al 13 showed that 30/45 subjects with normal CT findings at the craniocervical junction had abnormal findings on MR imaging. Seventeen of these patients, most younger than 8 years of age, had findings that met the criteria for "significant craniocervical junction injury," though the need for surgical management was not investigated in this study.…”
mentioning
confidence: 99%